2016
DOI: 10.1111/jphd.12168
|View full text |Cite
|
Sign up to set email alerts
|

Dentists' and dental students' attitudes, knowledge, preparedness, and willingness related to treatment of people living with HIV/AIDS in China

Abstract: It is imperative that knowledge of HIV/AIDS and attitudes toward PLWHA be further improved during dental training to increase the access to and effectiveness of dental care of PLWHA in China and to enhance their quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 27 publications
1
19
0
2
Order By: Relevance
“…En el presente estudio, se evidenció que, aunque gran parte de los académicos afirma conocer o haber tenido informaciones sobre el sida y la Hepatitis b, apenas poco más de la mitad de los académicos acertó el agente etiológico de las enfermedades. Ese análisis del conocimiento es semejante al de otros estudios realizados en China, Kuwait, Iraq, India, lo que demuestra que, aunque el asunto esté presente en los cursos de graduación, todavía existen lagunas sobre el tema que deben ser discutidas (16)(17)(18)(19).…”
Section: Resultadounclassified
See 1 more Smart Citation
“…En el presente estudio, se evidenció que, aunque gran parte de los académicos afirma conocer o haber tenido informaciones sobre el sida y la Hepatitis b, apenas poco más de la mitad de los académicos acertó el agente etiológico de las enfermedades. Ese análisis del conocimiento es semejante al de otros estudios realizados en China, Kuwait, Iraq, India, lo que demuestra que, aunque el asunto esté presente en los cursos de graduación, todavía existen lagunas sobre el tema que deben ser discutidas (16)(17)(18)(19).…”
Section: Resultadounclassified
“…Bogotá, Colombia, vol. 16 (2): 279-293, mayo-agosto de 2018 Discriminación y prejuicio. La influencia del vih/sida y Hepatitis b en la actitud de los académicos Introducción L a discriminación social es un fenómeno de gran impacto para el individuo, que debido a sus características fuera de los patrones morales, por su estereotipo negativo, ocasionan la pérdida de su individualidad y el rompimiento de los derechos humanos (1).…”
Section: Introductionunclassified
“…Increasing students’ awareness through community participation about social and financial determinants of poor oral health may aid them to appreciate the value of their professional contributions in providing care for underserved and medically indigent population. [2122] In our study, it is interesting to note that majority of the dental students responded that they tried to assess patients’ socioeconomic status before treatment. Students felt that assessing the socioeconomic status may guide to plan treatment accordingly.…”
Section: Discussionmentioning
confidence: 96%
“…Several studies published within the last ten years have described self‐reported beliefs and behaviours of dentists related to the provision of dental care for PLHIV. In China, almost half (44%) of dentists agreed that saliva was a vehicle for the transmission of HIV and more than three‐quarters (86%) wore extra personal protective equipment when treating PLHIV (Lee, Fan, Starr, & Dogon, 2017). Studies undertaken in North Africa and the Middle East suggested that there was concern from most dentists (81.5%) that transmission in the dental setting was very likely and there was a general uncertainty from the majority (82%) about their willingness to provide care for PLHIV (Alshouibi & AlAlyani, 2018; Arheiam et al., 2017).…”
Section: How Does Hiv Stigma Manifest In the Dental Setting?mentioning
confidence: 99%